Pengaruh Kepemimpinan Direktur Terhadap Produktifitas Kerja Tenaga Kependidikan di Akademi Maritim Cirebon - Susilawati (Jurnal Ilmu Pendidikan dan Sosial, 2023)
This study aims to determine whether the director's leadership has a positive influence on the work productivity of the teaching staff at the Cirebon Maritime Academy. The research method used in this research is a quantitative method to process the data obtained from the research location, namely data in the form of numbers or quantitative data that is raised. The sample used was 266 respondents consisting of all employees working in the AMC Cirebon environment and also students who were studying at AMC Cirebon which were taken using a non-probability sampling technique, namely the purposive sampling method, because in determining the sample in this study there were considerations criteria. The analysis used in this research is validity test, reliability test, simple linear regression, hypothesis testing with partial regression test (t test). Analysis using simple linear regression yields Y = 31.745 + 0.534X. It can be seen that the regression equation shows a positive effect of the leadership variable on the Work Productivity of Education Personnel at the Cirebon Maritime Academy. The results of the t test have a probability value of sig = 0.000 which is less than the probability value of 0.05 or a value of 0.05 ˃ 0.000 (then Ho is rejected and Ha is accepted, meaning that the regression coefficient is significant.